Image Super Resolution In View of Sparse Representation - Keerthi, PN; Shruthi, MK (International Journal of Computer Sciences and Engineering, 2025)
Sparse representation has attracted it interests in the field of image resolution. On small images with certain constraints the sparsity based methods enforce sparse coding. For the observed low resolution images it has certain limitations on small scale and different scales for image sparse representation. In this paper a joint super resolution framework has been proposed to improve sparsity based image performances. The algorithm proposed here optimizes the problem for high resolution image recovery. Both the ridge regression and the gradient histogram is incorporated to solve the problem.